Worm propagation model in mobile network. (5th June 2015) - Chen, Zhide; Wang, Meng; Xu, Li; Wu, Wei
Summary: With the popularity of mobile smart devices and functional diversification, the infection ways of mobile smartphones worm also become diverse. In mobile networks, mobile devices are suffering from the threat of worms all the time. Once the worm outbreaks, it will bring huge losses to mobile phone users and mobile network operators. Researches on mobile worm propagation model allow us to control and detect potential worm threat, according to the characteristics of worm's outbreak. In the paper, we put forward a worm propagation model based on the mobile network environment. After analyzing the model, we then give the simulation for controlling factors affecting worm propagation. This model allows us to have a certain understanding for the spread on the size and speed of the mobile worm and provide effective methods to control the spread of the mobile worm. Copyright © 2015 John Wiley & Sons, Ltd.